Fe3O4 – Glutathione stabilized Ag nanoparticles: A new magnetically separable robust and facile catalyst for aqueous phase reduction of nitroarenes. (4th September 2019) - Kumari, Mitlesh; Gupta, Ragini; Jain, Yachana
Abstract : The heterostructured Ag nanoparticles decorated Fe3 O4 Glutathione (Fe3 O4 ‐Glu‐Ag) nanoparticles (NPs) were synthesized by sonicating glutathione (Glu) with magnetite and further surface immobilization of silver NPs on it. The ensuing magnetic nano catalyst is well characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM), powder X‐ray diffraction (PXRD), thermogravimetric analysis (TGA). The prepared Fe3 O4 ‐Glu‐Ag nanoparticles have proved to be an efficient and recyclable nanocatalyst with low catalyst loading for the reduction of nitroarenes and heteronitroarenes to respective amines in the presence of NaBH4 using water as a green solvent which could be easily separated at the end of a reaction using an external magnet and can be recycled up to 5 runs without any significant loss in catalytic activity. Gram scale study for the reduction of 4‐NP has also being carried out successfully and it has been observed that this method can serve as an efficient protocol for reduction of nitroarenes on industrial level. Abstract : The heterostructured Ag nanoparticles decorated Fe3 O4 Glutathione (Fe3 O4 ‐Glu‐Ag) nanoparticles (NPs) were synthesized and well characterized and have proved to be an efficient and recyclable nanocatalyst with low catalyst loading for the reduction of nitroarenes and heteronitroarenes to respective amines in the presence of NaBH4 using water as a green solvent which could be easily separated at the end of a reaction using an external magnet and can be recycled up to 5 runs without any significant loss in catalytic activity.